2023
DOI: 10.7759/cureus.38199
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal Adenocarcinoma With Suspected Brain Metastasis

Abstract: Duodenal adenocarcinoma (DA) is a rare tumor. We present the case of an 84-year-old lady who presented with episodic emesis with progressive dysphagia to solids and liquids. She also noted a significant weight loss of 31kg over four months. She was reported to have multiple brain masses three months before this admission. A computed tomography (CT) scan showed a heterogeneous mass (8cm) in the left retroperitoneum, inseparable from the duodenum. Additional peritoneal nodules and enlarged retroperitoneal lymph … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…One case report reported a brain mass and biopsy-proven duodenal primary in an 84-year-old female patient. In that report, brain mass was not biopsy-proven as the patient opted for a palliative approach due to her elderly age [17]. Another case report reported the de novo presentation of jejunal adenocarcinoma with brain metastasis [15].…”
Section: Discussionmentioning
confidence: 96%
“…One case report reported a brain mass and biopsy-proven duodenal primary in an 84-year-old female patient. In that report, brain mass was not biopsy-proven as the patient opted for a palliative approach due to her elderly age [17]. Another case report reported the de novo presentation of jejunal adenocarcinoma with brain metastasis [15].…”
Section: Discussionmentioning
confidence: 96%
“…The accumulation of uranium has a signi cant impact on the germination, early growth of seedlings, photosynthesis, and metabolic and physiological functions of plants. [5]Geochemical processes, absorption and movement inside plants, harmful effects on plants, entry into the food chain, and ultimately, in uence on human well-being. Furthermore, alterations in the physico-chemical characteristics of soil and groundwater resulting from land use practices and shifts in climatic conditions after few decades also impact the presence of uranium in the terrestrial environment.[6-8].…”
Section: Introductionmentioning
confidence: 99%
“…This is partly due to the fact that some advanced patients reject the above treatment options for palliative care. 19 Surgical resection is currently the only treatment for DAC with curative potential. Ryder et al showed that the 5-year OS rate was 43% in DAC patients with tumor resection and only 13% in patients without tumor resection.…”
mentioning
confidence: 99%